2016
DOI: 10.1016/j.anbehav.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Using insights from animal behaviour and behavioural ecology to inform marine conservation initiatives

Abstract: The impacts of human activities on the natural world are becoming increasingly apparent, with rapid development and exploitation occurring at the expense of habitat quality and biodiversity. Declines are especially concerning in the oceans, which hold intrinsic value due to their biological uniqueness as well as their substantial sociological and economic importance. Here, we review the literature and investigate whether incorporation of knowledge from the fields of animal behaviour and behavioural ecology may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 239 publications
(270 reference statements)
0
26
0
Order By: Relevance
“…There has been increased call for conservation strategies to move beyond population‐based approaches in the conservation of marine systems being exposed to environmental change (Brooker et al., 2016; Killen et al., 2016). These laboratory results indicate that more effective and targeted strategies might indeed be designed by considering finer‐scale variation.…”
Section: Discussionmentioning
confidence: 99%
“…There has been increased call for conservation strategies to move beyond population‐based approaches in the conservation of marine systems being exposed to environmental change (Brooker et al., 2016; Killen et al., 2016). These laboratory results indicate that more effective and targeted strategies might indeed be designed by considering finer‐scale variation.…”
Section: Discussionmentioning
confidence: 99%
“…Studying animal behavior is a key aspect for species conservation because understanding their behavioral plasticity and how it will change with respect to anthropogenic impacts in the future is crucial. It has become a growing field in research, as the fitness and social structure of species can be disrupted when behavior is changed as a consequence of environmental factors (Brooker et al, 2016). Researching behavior for all species would be ideal, but there is a recorded bias toward vertebrates in temperate regions, because studies are often done on charismatic animals that the public tend to favor in areas that are geographically easy to access (Titley et al, 2017;Davies et al, 2018).…”
Section: Animal Behavior Researchmentioning
confidence: 99%
“…Marine invertebrates are often overlooked in this field, but they are important species to study as climate change becomes a larger issue, since many are useful bioindicators and play a major role in the food web. Marine invertebrates are also interesting for animal behavior research because the larval stages of marine species oftentimes have well-developed behaviors that allow them to postpone their settlement until reaching a suitable habitat (Rahman et al, 2014;Brooker et al, 2016). However, phenological changes in behavior due to ocean warming compounded with the sessile nature of adult invertebrates, may potentially result in higher mortality rates; as Fuchs et al (2020) found in its study, many invertebrate species have been discovered moving toward warmer water along the coast instead of escaping into colder waters.…”
Section: Animal Behavior Researchmentioning
confidence: 99%
“…This emphasis on terrestrial fauna is likely an artifact of the logistical challenges of studying marine organisms, especially those which display complex and cryptic life histories. Considering the multitude of threats facing marine ecosystems (Cózar et al 2014, McCauley et al 2015, Molinos et al 2016), understanding how ecological niches have evolved is intricately tied to our ability to identify vulnerable taxa, predict how associated distributions and functional roles are likely to change over time, and understand how protecting specific niches may help preserve marine biodiversity (Brooker et al 2016).…”
Section: Introductionmentioning
confidence: 99%